Direct fluorescent labeling of NF186 and NaV1.6 in living primary neurons using bioorthogonal click chemistry: tools and resources - Stajković, Nevena; Liu, Yuanyuan; Arsić, Aleksandra; Meng, Ning; Lyu, Hang; Zhang, Nan; Grimm, Dirk; Lerche, Holger; Nikić-Spiegel, Ivana (Journal of cell science, 2023)
The axon initial segment (AIS) is a highly specialized neuronal compartment that regulates the generation of action potentials and maintenance of neuronal polarity. Live imaging of the AIS is challenging due to the limited number of suitable labeling methods. To overcome this limitation, we established a novel approach for live labeling of the AIS using unnatural amino acids (UAAs) and click chemistry. The small size of UAAs and the possibility of introducing them virtually anywhere into target proteins make this method particularly suitable for labeling of complex and spatially restricted proteins. Using this approach, we labeled two large AIS components, the 186 kDa isoform of neurofascin (NF186; encoded by Nfasc) and the 260 kDa voltage-gated Na+ channel (NaV1.6, encoded by Scn8a) in primary neurons and performed conventional and super-resolution microscopy. We also studied the localization of epilepsy-causing NaV1.6 variants with a loss-of-function effect. Finally, to improve the efficiency of UAA incorporation, we developed adeno-associated viral (AAV) vectors for click labeling in neurons, an achievement that could be transferred to more complex systems such as organotypic slice cultures, organoids, and animal models.